Integrated Maqasid Al-Shariah in Cash Waqf Linked Deposit: A Study Approach to Sustainable - Tumanggor, Dian Valentina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
To strengthen the characteristics of Islamic banking and increase its contribution to the national economy, OJK developed a unique Islamic product called Cash Waqf Linked Deposit (CWLD). This research aims to investigate the effects of CWLD empowerment programs on the welfare of beneficiaries, financial inclusion, social participation, and spiritual growth, aligning with the principles of Maqasid al-Shariah. These principles focus on poverty eradication, social justice, and economic welfare through Hifze deen (faith preservation), Hifze maal (wealth preservation), and providing the poor with access to productive resources like education, training, and credit. The study examines OJK's initiative to enhance Islamic bank participation in cash waqf management for sustainable finance and broader objectives of Maqasid al-Shariah. In-depth interviews with seven key figures (two donors, three waqf institution representatives, and two managers) are analyzed using NVivo software. The findings reveal a high level of alignment between the proposed CWLD product design and stakeholder expectations. This strong alignment underscores the product's capacity to meet the objectives of Maqasid al-Shariah, such as poverty eradication, social justice, and economic welfare. By addressing these fundamental Islamic principles, the CWLD product contributes to sustainable finance, ensuring that financial activities support long-term economic stability, social inclusion, and environmental sustainability.